The Effectiveness Preconception Care To Improve Knowledge On Pregnancy : A Systematic Review - Maria, Rulfia Desi; Sansuwito, Tukimin Bin; Umar, Nur Syazana (International Journal of Health Sciences, 2023)
Introduction: Preconception services for prospective brides and grooms are an important thing that must be provided as an effort to increase the knowledge of prospective brides, including insight into preparations before marriage. It is hoped that with the insights and knowledge gained, prospective brides and grooms can build a healthy and safe married life, with the aim that readers can get an overview of the knowledge of prospective male and female couples by knowing the effectiveness of providing education regarding contraceptive services. Materials and Methods: The method used was a literature review where data was obtained from an electronic database, namely Google Scholar, Pubmet, Scopus between 2018-2023 have 68 after check the articles were found, 7 articles were selected that were in accordance with the objectives of this research. Results: The results obtained from the study of the article on readiness to face a first pregnancy come from the preparations made by the prospective bride and groom before marriage and pregnancy, communication of information and education regarding reproductive health and readiness to face their first pregnancy is very effective and is very necessary for the prospective bride and groom to have good preparedness. During preconception services, during the first pregnancy, many women are not ready to face pregnancy because they do not have good knowledge and previous experience. Conclusion: The local Religious Affairs Office makes reproductive health material mandatory material that must be conveyed to prospective brides and grooms and can revitalize cooperation with related parties regarding health material education.